Cutaneous metastases of invasive lobular breast cancer as the first clinical manifestation: a case report - Saja Karaja; Ahmad Almohamed; Ayham Qatza; Ahmed Aldolly; Sanaa Mansour; Alae Aldin Almasri (Journal of International Medical Research)
Cutaneous metastasis (CM) is a rare phenomenon, occurring in only 0.6% to 10.4% of oncology patients. Breast carcinoma represents nearly one-third of all CM cases, although it manifests in a minority of patients with breast cancer (BC). Notably, CMs are detected at the time of primary tumor diagnosis in 6.3% of patients with BC and serve as the initial clinical presentation in only 3.5% of patients. We present a case involving a 53-year-old woman with a 5-month history of asymptomatic infiltrating nodules in the axillae and trunk. Skin biopsy and immunohistochemical analysis confirmed metastatic breast carcinoma with positive estrogen receptor staining. This case underscores the importance of early detection and precise diagnostic techniques in managing metastatic adenocarcinoma with cutaneous manifestations. Despite the promising outcome of the initial treatment, the disease progression in this case highlights the aggressive nature of CMs and the ongoing need for research and advanced therapeutic strategies.